The development of the english language: The process of creating new vocabulary from existing ones / Kamisah Hj Ariffin - Hj Ariffin, Kamisah (Universiti Teknologi MARA Cawangan Pahang, 2002)
When Julius Caesar landed in Britain over two thousand years ago, the English Language did not exist (McRum et al, 1992). At present, the contrast is remarkably extraordinary. This language is used by at least 750 million people, and half of those speak it as a mother tongue. On top of that, English is claimed to be the richest in vocabulary. The Oxford English Dictionary lists about 500,000 words, and a further half-million technical and scientific terms remain uncatalogued. However, the development process of the language has not happened in a vacuum. This paper examines the processes of creating new words in the English vocabulary.